2003
DOI: 10.1071/bt02008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthesis during leaf expansion in Corymbia gummifera

Abstract: Growth, pigment levels and various photosynthesis parameters were measured in expanding leaves of Corymbia gummifera (Solander ex Gaertner) Hochreutiner. C. gummifera trees were studied growing in sandstone plateau woodland communities in Royal National Park, New South Wales, in a recently burned open habitat. Young leaves (horizontally oriented to maximise light exposure) were found to be conspicuously red until they reached approximately 75% of their full size. As the leaves expanded, anthocyanin content dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 28 publications
2
34
1
3
Order By: Relevance
“…2a). This suggests that photosynthetic metabolism was gradually perfected along with leaf area expanding, and similar result also has been obtained in the studies on other plants (Roper and Kennedy 1986;Choinski et al 2003;Jiang et al 2006a, b, c;Maayan et al 2008). Stomatal conductance determines entry of CO 2 into the leaf and closely associates with Pn, and the close relation between Gs and Pn has been demonstrated in Ficus carica during leaf development recently (Gonzalez-Rodriguez and Peters 2010).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…2a). This suggests that photosynthetic metabolism was gradually perfected along with leaf area expanding, and similar result also has been obtained in the studies on other plants (Roper and Kennedy 1986;Choinski et al 2003;Jiang et al 2006a, b, c;Maayan et al 2008). Stomatal conductance determines entry of CO 2 into the leaf and closely associates with Pn, and the close relation between Gs and Pn has been demonstrated in Ficus carica during leaf development recently (Gonzalez-Rodriguez and Peters 2010).…”
Section: Discussionsupporting
confidence: 63%
“…Thus, we suppose that leaf area expansion process also involved the synthesis and assembly of photosynthetic apparatus in Jerusalem artichoke. So far, it is not definite whether primary photochemical reaction of PSII is the limiting step of photosynthetic capacity during the leaf growth, as contradictory results have been reported in different plants (Lebkuecher et al 1999;Srivastava et al 1999;Choinski et al 2003;Jiang et al 2005Jiang et al , 2006c. These contradictory results can be attributed to the inconsistent culture protocol or plant species.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…On the contrary, in mature leaves, more absorbed light was dissipated by thermal dissipation processes associated to xanthophylls cycle (higher  NPQ ). This result is in contrast with data reported by other authors who found a reduction in thermal dissipation by xanthophylls cycle as the leaves expanded (Choinski & Eamus, 2003;Jiang et al, 2005). Our data suggest that leaf age influences the photoprotection mechanisms.…”
Section: Young and Mature Leaves Of Laurus Nobilis L Phillyrea Angucontrasting
confidence: 57%
“…However, chlorophyll content can vary widely with leaf age in eucalypts (Choinski Jr et al 2003, Close et al 2004) and other genera (Mohammed et al 2000, Sims andGamon 2002). In eucalypts a common response to stress is production of anthocyanins, for example during photoinhibitory conditions (Close and Beadle 2003) or from biotic leaf damage (Stone et al 2000, Smith et al in press).…”
Section: Detection Of Stress In Eucalyptsmentioning
confidence: 99%